CHRISTOPHER MARLOWE’S “CARP DIEM POETRY” - Xamrayev Sevinch Zarifboyevna; Kenjayeva Muxlisa Bahadirovna (Ta'lim innovatsiyasi va integratsiyasi, 2024)
This article delves into the thematic exploration of temporality in Christopher Marlowe's poetry, particularly focusing on his adept use of the "Carpe Diem" motif. Marlowe, a renowned Elizabethan playwright and poet, masterfully weaves the concept of seizing the day into his works, urging readers to embrace the present moment and live life to the fullest. Through close analysis of select poems such as "The Passionate Shepherd to His Love" and "The Nymph's Reply to the Shepherd," this study highlights Marlowe's intricate manipulation of language and imagery to evoke a sense of urgency and impermanence. Additionally, it examines the socio-historical context of Marlowe's era and its influence on his portrayal of time and mortality. By engaging with Marlowe's "Carpe Diem" poetry, readers gain insight into the enduring relevance of his works and their timeless appeal.